Exploring saiga horn consumption in Singapore - Theng, M; Glikman, J; Milner-Gulland, E (Cambridge University Press, 2018)
The Critically Endangered saiga antelope Saiga tatarica faces an uncertain future, with populations dwindling from epidemics in its range countries, and ongoing demand for its horns in the traditional Chinese medicine trade. Singapore is a major hub for the global trade in saiga horn and an important consumer country, with saiga horn products widely available in the domestic market. Despite this, little is known about the consumers that drive domestic demand. Before interventions are carried out, it is important to understand who the consumers are, and their motivations. We conducted an investigation into consumption prevalence and consumer demographics, knowledge and motivations. We surveyed 230 Chinese Singaporeans, through a combination of face-to-face interviews and self-administered questionnaires. Recent consumption incidence (in the previous 12 months) was relatively high, at 13%. Younger respondents (18–35 years) had the highest prevalence of recent consumption (25%), often as a result of influence from an older family member or friend. Bottled saiga horn cooling water was the most popular product among recent users (50%), followed by horn shavings (31%) and tablets (13%). Awareness of conservation issues and regulations was uniformly low. Awareness raising may have an effect in reducing consumer demand in Singapore. However, given the exploratory nature of this study, it is best used to guide and inform future research underlying behavioural change interventions in a relatively understudied but important consumer group, Chinese Singaporeans.